Pyrite Passivation by Triethylenetetramine: An Electrochemical Study - Yun Liu; Zhi Dang; Yin Xu; Tianyuan Xu (Journal of Analytical Methods in Chemistry)
The potential of triethylenetetramine (TETA) to inhibit the oxidation of pyrite in H2SO4 solution had been investigated by using the open-circuit potential (OCP), cyclic voltammetry (CV), potentiodynamic polarization, and electrochemical impedance (EIS), respectively. Experimental results indicate that TETA is an efficient coating agent in preventing the oxidation of pyrite and that the inhibition efficiency is more pronounced with the increase of TETA. The data from potentiodynamic polarization show that the inhibition efficiency (η%) increases from 42.08% to 80.98% with the concentration of TETA increasing from 1% to 5%. These results are consistent with the measurement of EIS (43.09% to 82.55%). The information obtained from potentiodynamic polarization also displays that the TETA is a kind of mixed type inhibitor.